2010
DOI: 10.1176/appi.ap.34.4.305
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Residents as Teachers: Development and Evaluation of a Teaching Manual

Abstract: The development of, and the preliminary survey of this psychiatric resident teaching manual, is encouraging in furthering the development of future psychiatrist teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…. Objectives for a TA elective within the framework of a basic science course interaction (Dewey et al 2008;Post et al 2009;Swainson et al 2010). The significant increase in the literature regarding ''residents as teachers'' (Mann et al 2007;Dewey et al 2008;Post et al 2009) highlights the importance of providing opportunities and implementing guidelines for continuing medical education and professional growth.…”
Section: Practice Pointsmentioning
confidence: 99%
“…. Objectives for a TA elective within the framework of a basic science course interaction (Dewey et al 2008;Post et al 2009;Swainson et al 2010). The significant increase in the literature regarding ''residents as teachers'' (Mann et al 2007;Dewey et al 2008;Post et al 2009) highlights the importance of providing opportunities and implementing guidelines for continuing medical education and professional growth.…”
Section: Practice Pointsmentioning
confidence: 99%
“…Luego de eliminar los duplicados (n=75) se revisaron los títulos y resúmenes de 1085 artículos, de los cuales, 18 fueron analizados en texto completo. Luego de esta lectura, 11 fueron excluidos por los siguientes motivos: cinco eran revisiones narrativas (16)(17)(18)(19)(20); dos hacían referencia a estudiantes de pregrado en medicina (21)(22) y uno en profesores (23); dos eran estudios primarios (24-25) y el otro era una carta al editor (26). Finalmente, se incluyeron siete revisiones sistemáticas (3-5 8, 13, 27-28).…”
Section: Resultsunclassified
“…25 Swainson and co-authors identified residents' difficulty in determining what to teach students and how to teach them. 26 In our survey psychiatry trainees rated themselves more confident in teaching the mental state examination and psychiatric history, the areas where they themselves are taught. They reported lower levels of confidence in approaching difficulties with students and in their overall view of themselves as educators.…”
Section: Psychiatry Trainees and Clinical Teachingmentioning
confidence: 92%